COMPARATIVE ANALYSIS OF THE POLISH AND FRENCH CIVIL CODES - BETAŃSKA, Ewa (Comparative Legilinguistics, 2011)
The Civil Code is one of the most important statutory instruments regulating civil matters in Poland and France. The aim of the paper is to make the readers acquainted with the development of the civil code in Poland and France and to show the impact of the French Code civil on the contemporary Polish legal language. The author presents techniques of providing equivalents for non-equivalent terminology applied in the translation of the Code rendered by F.K. Szaniawski in 1808. It is stressed here that despite the fact that borrowings, as a technique of providing equivalents which is highly criticised, still affected the Polish legal language (e.g. hipoteka [hypothèque], pupil [pupille], inwentarz [inventaire], testator [testateur]).